Clinical and radiological activity of secondary progressive multiple sclerosis in a population‐based cohort. (18th May 2021) - Mathey, Guillaume; Ancel, Thomas; Garot, Teresa; Soudant, Marc; Pittion‐Vouyovitch, Sophie; Guillemin, Francis; Debouverie, Marc; Epstein, Jonathan
Abstract: Background and purpose: Patients with secondary progressive multiple sclerosis (SP MS) and clinical and/or radiological activity could be the more likely to benefit from disease‐modifying treatments. To evaluate the proportions each year after progression onset, patients with SP MS onset between 2002 and 2012 from a population‐based multiple sclerosis registry in northeastern France were studied. Methods: Progression onset was first identified by the neurologist's diagnosis (N cohort), and then by using an automated data‐driven definition (D cohort). In a given year after onset of progression, clinical activity was defined as at least one relapse, and radiological activity as at least one new T2 and/or gadolinium‐enhancing lesion. A multivariate mixed logistic regression was used to assess factors associated with activity during the year. Results: In the N cohort, amongst 833 patients with SP MS with a median follow‐up of 8 years, 10.0%–14.8% had at least one relapse in a year during the first 5 years of progression. Including both clinical and radiological activity increased these proportions to 11.9%–23.7%, with the proportion having a magnetic resonance imaging scan in the year ranging from 29.8% to 40.5%. The first year of progression, a young age and a high relapse rate during the 5 years before progression were associated with activity in a given year. The D cohort results confirmed these findings. Conclusions: A substantial proportion of patients with SP MS present disease activity. Further studies should evaluate the impact of disease‐modifying treatments on the disease course of these patients. Abstract : Amongst 833 French patients with secondary progressive multiple sclerosis with a median follow‐up of 8 years, 10.0%–14.8% had at least one relapse in a year during the first 5 years of progression. Including both clinical and radiological activity increased these proportions to 11.9%–23.7%.